Evaluation of pharmaceutical cream production debottlenecking schemes - Tan, Jully; Foo, Dominic Chwan Yee; Kumaresan, Sivakumar; Abdul Aziz, Ramlan (2005)
The main objective of this work is to model and debottleneck a pharmaceutical production of an anti-allergic cream. The base case process has a minimum cycle time of 29 hours which is equivalent to 66 batches/year. Four schemes were proposed for process debottlenecking due to the anticipated increase of the product demand of 150% in the market. By carrying out throughput analysis study, schemes that fulfil the debottlenecking objective were determined. Out of the four debottlenecking schemes, Scheme 4 was chosen, which proposed a new blending tank and intermediate tank, showed a production increase of over 150%.